Painless Loss of Vision as The First Presentation of Undiagnosed Neurofibromatosis 1 in A Child - PAUL, Siba Prosad; AHMED, Shameem (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Paul SP, Ahmed S, Painless Loss of Vision as The First Presentation of Undiagnosed Neurofibromatosis 1 in A Child. Iran J Child Neurol. Autumn 2015;9(4):58-60. Abstract Objective A 10 year old presented with painless loss of vision as the first manifestation of neurofibromatosis 1 (NF1). Clinical assessment detected diagnostic features of NF1 and Magnetic Resonance Imaging (MRI) scan confirmed presence of plexiform neurofibroma and bilateral optic pathway glioma (OPG). The child was managed with chemotherapy which helped in improvement of vision. Review of current literature recommends vision testing in diagnosed cases of NP1 till 7 years of age; this is aimed at detecting visual impairments resulting from a symptomatic OPG.